Nazi policy on the Eastern Front, 1941 : total war, genocide, and radicalization - Kay, Alex J. 1979- HerausgeberIn; Rutherford, Jeff HerausgeberIn; Stahel, David 1975- HerausgeberIn (Rochester studies in Central Europe, 2012)
Foreword by Christian Streit -- Introduction / Alex J. Kay, Jeff Rutherford, and David Stahel -- Radicalizing warfare : the German command and the failure of Operation Barbarossa / David Stahel -- Urban warfare doctrine on the Eastern Front / Adrian E. Wettstein -- The Wehrmacht in the war of ideologies : the army and Hitler's criminal orders on the Eastern Front / Felix R?mer -- "The purpose of the Russian Campaign is the decimation of the Slavic population by thirty million" : the radicalization of German food policy in early 1941 / Alex J. Kay -- The radicalization of German occupation policies : the Wirtschaftsstab Ost and the 121st Infantry Division in Pavlovsk, 1941 / Jeff Rutherford -- The exploitation of foreign territories and the discussion of Ostland's currency in 1941 / Paolo Fonzi -- Axis collaboration, Operation Barbarossa, and the Holocaust in Ukraine / Wendy Lower -- The radicalization of anti-Jewish policies in Nazi-occupied Belarus / Leonid Rein -- The Minsk experience : German occupiers and everyday life in the capital of Belarus / Stephan Lehnstaedt -- Extending the genocidal program : did Otto Ohlendorf initiate the systematic extermination of Soviet "gypsies"? / Martin Holler -- The development of German policy in occupied France, 1941, against the backdrop of the war in the east / Thomas J. Laub -- Conclusion : total war, genocide, and radicalization / Alex J. Kay, Jeff Rutherford, and David Stahel